1993
DOI: 10.1139/g93-092
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogeny analysis of Azolla based on DNA amplification by arbitrary primers

Abstract: The polymerase chain reaction was used to amplify random sequences of DNA from 25 accessions of Azolla to evaluate the usefulness of this technique for identification and phylogenetic analysis of this aquatic fern. Accessions were selected to represent all known species within the genus Azolla and to encompass the world-wide distribution of the fern. Primers of 10 nucleotides with 70% G + C content were used to generate randomly amplified polymorphic DNA from the symbiotic Azolla-Anabaena complex. Twenty-two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…(2) primer S17 (3) primer OPE6 (4) primer OPB12 (A1 and A2, B1 and B2, C1 and C2 refer to two individuals of Muraenesox cinereus, Anguilla anguilla and Anguilla japonica) DISCUSSION RAPD employs single arbitrarily chosen primers and the polymerase chain reaction ( PCR), and is useful in fingerprinting complex genomes. By RAPD a set of primers can generate multiple genetic markers to distinguish closely related species or even strains [ 8], [9] . In this study, 29 random primers were applied to measure the polymorphisms between Anguilla japonica, Anguilla anguilla and Muraenesox cinersus.…”
Section: Resultsmentioning
confidence: 99%
“…(2) primer S17 (3) primer OPE6 (4) primer OPB12 (A1 and A2, B1 and B2, C1 and C2 refer to two individuals of Muraenesox cinereus, Anguilla anguilla and Anguilla japonica) DISCUSSION RAPD employs single arbitrarily chosen primers and the polymerase chain reaction ( PCR), and is useful in fingerprinting complex genomes. By RAPD a set of primers can generate multiple genetic markers to distinguish closely related species or even strains [ 8], [9] . In this study, 29 random primers were applied to measure the polymorphisms between Anguilla japonica, Anguilla anguilla and Muraenesox cinersus.…”
Section: Resultsmentioning
confidence: 99%
“…This makes it a tool of great power and general applicability. It has been shown that as few as three primers used separately provide enough polymorphic information to identify species of the symbiotic genus Anabaena and to create a phylogenetic tree with topology similar to that derived with 22 primers (van Coppenhole et al 1993). Similarly, a single 10-mer and 8-mer proved sufficient for distinguishing among 31 symbiotic cyanobacterial strains of Phaeoceros sp.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, in recent years, the cyanobacteria inhabiting the different Azolla species have been classified using different molecular markers either directly on isolated DNA from the intact symbiosis or by PCR analysis of intact filaments picked out from the leaf cavities (Plazinski et al, 1990;van Coppenolle et al, 1993;Caudales et al, 1995;Kim et al, 1997;Zheng et al, 1999). These investigations show that the cyanobacteria from the Azolla and Rhizosperma sections are clearly distinguishable.…”
Section: The Cyanobiontmentioning
confidence: 99%